Trig

posted by .

4tan^2u-1=tan^2u

3tan^2u=1

tan^2u=1/3

sq. root of (tan^2u)=sq. root of (1/3)

tanu=sq. root of (3)/3

tanu=sq. root of 1

Did I do this one right? If not, could you please show me the correct method??
Thanks!

• Trig -

I don't understand your last step.
From tanu=sq. root of (3)/3
The next step would be
u = tan^-1[1/(sqrt3)]= 30 degrees
(or 210 degrees)

Your first steps are OK, until the last line.

Similar Questions

1. math

tan (u-v) given sin u=3/4 and cos v= -5/13 with U and V in quadrant 2 Use the identity tan (u-v) = (tanu tanv)/[1-tanu tanv) Get the values of tanu and tanv from the sines and cosines that you are given. For example, if cos v = -5/13, …
2. Algebra

I had to solve 2x^2-x-1 using the quad. formula. I got it down to (1 +/- the square root of neg. 8) divided by four. I broke the sq. of neg. 8 into the sq. root of 4 and the sq. root of -2. But my question is could it also be the sq. …
3. Trig.

sec^2xcotx-cotx=tanx (1/cos)^2 times (1/tan)-(1/tan)=tan (1/cos^2) times (-2/tan)=tan (-2/cos^2tan)times tan=tan(tan) sq. root of (-2/cos^2)= sq. root of (tan^2) sq. root of (2i)/cos=tan I'm not sure if I did this right. If I didn't, …
4. trig

Given that tan 45=1, use tan(x+y) to show that tan 22.5= /2 - 1. (/is square root sign
5. Calc

y= cube root (1+tan(t)) OR y= (1+tan(t))^(1/3) The answer I got was y'= (1/3)(1+tan(t))^(-2/3)*(sec^2(t)) Is this correct?
6. Algebra II

Multiple Choice (theta) means the symbol 0 with the dash in it. 1.)Which expression is equivalent to tan(theta)-(sec(theta))/(sin(theta))?
7. math

Use the exact values of the sin, cos and tan of pi/3 and pi/6, and the symmetry of the graphs of sin, cos and tan, to find the exact values of sin -pi/6, cos 5/3pi and tan 4pi/3. I have found the answers to the first three using the …
8. calculus

Show that tan^3(x)-8(tan^2(x))+17(tan(x)0-8 = 0 has a root in [0.5, 0.6]. Apply the Bisection Method twice to find an interval of length 0.025 containing this root. I have NO idea where to go with that equals 0 part...I could figure …
9. mathematics

1.)Sin^-1(x)+Sin^-1(y)+Sin^-1(z)= pie Prove that X.root(1-y^2)+y.root(1-x^2)+z.root(1-z^2)=2xyz 2.)tan^-1(yz/xr)+tan^-1(zx/yr)+tan^-1(xy/zr)=pie/4 Prove that x^2+y^2+z^2=r^2 Tomorrow is my exam.please give me answer as soon as possible.